Jurisprudential Issues Derived from Verse (114) of Surah Al-Baqarah – A Comparative Study (Islamic Sciences Journal, 2025)
This research presents a detailed jurisprudential analysis of one of the most profound verses of admonition in the Glorious Quran: Verse 114 of Surah Al-Baqarah. The study focuses on elucidating the linguistic and legal concepts embedded in the verse, extracting jurisprudential rulings, and examining the perspectives of classical and contemporary scholars.The research addresses several key themes, including:·  Explanation of uncommon terms in the verse.·  The diversity of Quranic recitations (Qira’at) and their impact on meaning.·  Methodologies for deriving jurisprudential rulings from Quranic texts.·  The role of rhetorical pauses (Fawasil) in shaping derived rulings.The study also explores the primary jurisprudential issues derived from the verse, such as:·  The prohibition of preventing Muslims from performing acts of worship in mosques.·  The prohibition of causing harm to mosques or seeking their destruction.·  The obligation to preserve mosques.·  The severe punishment for violating the sanctity of mosques.The research concludes with a contemporary case study (a jurisprudential issue) regarding the suspension of congregational prayers in mosques due to pandemics like COVID-19. It highlights the differing opinions among modern scholars on the permissibility of such suspensions and the jurisprudential guidelines supporting each viewpoint.
Keywords: Jurisprudential issues, derived rulings, Surah Al-Baqarah, comparative study